Web-based applications to develop students’ creativity in English for specific purposes - Iryna Simkova; Oleksandra Bondarenko; Lina Bielovetska (International Journal of Evaluation and Research in Education (IJERE), 2021)
This paper investigates the implementation of web-based applications to develop students’ creative thinking skills in English for Specific Purposes. The paper explores the role of web-based applications during creativity development in English for Specific Purposes classes. The attention is paid to the analysis of organizational levels of creative thinking development and concepts of creativity. This paper discusses how to achieve creative thinking during distance learning in English for Specific Purposes classes. The sample was 310 bachelor students from two Ukrainian universities. The sample was selected on the basis of the stratified sampling technique. The instruments were used F-test, the Likert-type scale test, and interviews. The study presents the results gained from interviews with Ukrainian students and results of creativity tests passed by students. The examples of tasks aimed at creative thinking achievement during distance learning in English for Specific Purposes classes are given. A comparative analysis of results has allowed emphasizing the positive experience of two Ukrainian universities, which can be implemented in future distance learning in the higher institutions located in other regions of Ukraine. The findings of this study support the idea that the development of creative thinking skills during the distance learning of bachelor students of different specialism can be intensified with the selection of proper web-based applications.